2020
DOI: 10.1002/ijc.33191
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of colorectal cancer risk based on profiling with common genetic variants

Abstract: Increasing numbers of common genetic variants associated with colorectal cancer (CRC) have been identified. Our study aimed to determine whether risk prediction based on common genetic variants might enable stratification for CRC risk. Metaanalysis of 11 genome-wide association studies comprising 16 871 cases and 26 328 controls was performed to capture CRC susceptibility variants. Genetic prediction models with several candidate polygenic risk scores (PRSs) were generated from Scottish CRC case-control studie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 25 publications
(43 reference statements)
2
22
0
Order By: Relevance
“…In summary, we have found that stratifying colorectal cancer risk by including a PRS with firstdegree family history results in an improved risk prediction compared with using family history alone for a sample that mirrors the general population, for which <15% had a family history. This is in agreement with previous studies that have also shown that a PRS adds substantial value in colorectal cancer risk stratification and explains a sizeable excess risk of colorectal cancer, independent of family history (17,48). Our new data strengthens the argument for clinical application of polygenic risk assessment in the general population, and especially for those without a family history, and supports the expansion of current recommendations that focus only on family history and age as the main criteria for screening.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In summary, we have found that stratifying colorectal cancer risk by including a PRS with firstdegree family history results in an improved risk prediction compared with using family history alone for a sample that mirrors the general population, for which <15% had a family history. This is in agreement with previous studies that have also shown that a PRS adds substantial value in colorectal cancer risk stratification and explains a sizeable excess risk of colorectal cancer, independent of family history (17,48). Our new data strengthens the argument for clinical application of polygenic risk assessment in the general population, and especially for those without a family history, and supports the expansion of current recommendations that focus only on family history and age as the main criteria for screening.…”
Section: Discussionsupporting
confidence: 91%
“…There were few incident cases in participants in their 40s. This affected our ability to confirm published evidence(17,48,57), suggesting superior clinical utility in PRS to help detect early-onset colorectal cancer before age 50 years; we observed a not significant trend in the expected direction for the few young age at diagnosis cases (S2 Table). Furthermore, a recently published study (58) has identified, using exome data, 76 participants in the UK biobank who are potential Lynch syndrome carriers, 17 of whom are cases.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…In the past 2 decades, genome-wide association studies (GWASs) have identified a rapidly increasing number of single nucleotide polymorphisms (SNPs) that are independently associated with the risk of colorectal cancer (CRC) ( 1‐8 ). Recent studies have shown that polygenic risk scores (PRS) built from these SNPs may be useful for CRC risk prediction and risk stratification for personalized screening ( 9 , 10 ). Furthermore, a prior study suggested that people with high genetic risk are most likely to benefit from the targeted CRC screening strategies ( 11 ).…”
mentioning
confidence: 99%
“…Large GWAS have identified more than 100 loci associated with an increased risk of CRC. [7][8][9] However, most of the loci confer low risk and do not explain the seemingly increased risk in cancer families. Therefore, when massive parallel sequencing became possible, families have been used for studies using whole-exome sequencing (WES) and whole genome sequencing (WGS) to find the responsible genes.…”
mentioning
confidence: 99%